2021
DOI: 10.1016/j.rgmxen.2021.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Severe bowel complications in SARS-CoV-2 patients receiving protocolized care

Abstract: Introduction and aims A case series of ten patients that received protocolized care for SARS-CoV-2 infection and developed severe gastrointestinal complications, is presented. The aim of our study was to contribute to the ongoing discussion regarding gastrointestinal complications related to SARS-CoV-2 infection. After reviewing the current literature, ours appears to be the first detailed case series on the topic. Materials and methods A retrospective filtered search o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Gastrointestinal features in COVID-19 disease are relatively frequently reported, varying from less than 10% in early studies from China [ 7 , 8 ] to 30–60%, in other reports [ 9 , 10 ]. In an extensive study on 1992 hospitalized patients for COVID-19 pneumonia from 36 centers, Elmunzer et al [ 7 ] found that the most frequent clinical signs reported were mild and self-limited in up to 74% of cases, consisting of diarrhea (34%), nausea (27%), vomiting (16%), and abdominal pain (11%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastrointestinal features in COVID-19 disease are relatively frequently reported, varying from less than 10% in early studies from China [ 7 , 8 ] to 30–60%, in other reports [ 9 , 10 ]. In an extensive study on 1992 hospitalized patients for COVID-19 pneumonia from 36 centers, Elmunzer et al [ 7 ] found that the most frequent clinical signs reported were mild and self-limited in up to 74% of cases, consisting of diarrhea (34%), nausea (27%), vomiting (16%), and abdominal pain (11%).…”
Section: Introductionmentioning
confidence: 99%
“…However, the significance of fecal elimination of viral ARN is still not fully understood in the transmission chain of the SARS-CoV-2 infection. On the other hand, disturbance of lung-gut axis, prolonged hospitalization in ICU, and the pro coagulation state induced by SARS-CoV-2 endothelial damage was incriminated for bowel ischemia, resulting in intestinal necrosis and perforation [ 8 , 9 , 15 ]. Early recognition and treatment of gastrointestinal ischemia are extremely important, but it is often challenging in hospitalized COVID-19 patients with severe illness.…”
Section: Introductionmentioning
confidence: 99%
“…By international consensus, as recorded in treatment guidelines by both the WHO and the NIH, corticosteroids are incorporated in the standard care protocol for COVID-19 [55,56]. Although no evidence suggests an increased risk in intestinal ischemia due to steroid therapy, increased risk of gastrointestinal perforation and an increased mortality and morbidity in the context of bowel perforation and bowel surgery has been described [39]. In our series, two patients developed anastomotic or stump leakage after surgery, one of whom was receiving corticosteroids at the time of ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our findings can also be attributed to COVID-19 having extrapulmonary manifestations. For example, several studies showed that COVID-19 enters digestive cells through ACE-2 receptors and can cause a myriad of responses, such as inflammation and gut microbial dysbiosis [ 16 , 17 ]. Case reports have even reported that COVID-19 can exacerbate underlying gastrointestinal ailments, leading to complications, such as bowel perforation [ 11 , 17 ].…”
Section: Discussionmentioning
confidence: 99%